Penerapan Design Thinking dalam Pengembangan Aplikasi Mobile Penjualan Kosmetik dan Manajemen Inventori Kadaluarsa: Studi Kasus Toko ANHA - annisa, annsa rahma cahyani woretma; Sakinah, Nur; Fachruddin, Muh.; Saputri, Tri Bata Biru; Basri, Hasan (Jurnal Informasi, Sains dan Teknologi, 2025)
Digital transformation is an urgent need for MSMEs to maintain competitiveness, yet many businesses like Toko ANHA Kosmetik still rely on manual operational systems that pose a high risk of inefficiency and losses due to expired products. This study aims to design and develop a mobile-based cosmetic sales application capable of integrating inventory management with an early warning feature for product expiration. The methodology employed is Design Thinking, encompassing the stages of empathize, define, ideate, prototype, and test to ensure the solution is user-centered. The results indicate that this approach successfully identified the primary pain points of the store owner and translated them into functional features such as automatic T-30 expired date notifications and digital product catalogs. System testing was conducted using Black Box Testing, yielding 100% functional validity, and User Acceptance Testing (UAT), which resulted in an average score of 83.49%, categorized as "Excellent." This study concludes that the designed application is not only technically effective in preventing operational losses but also highly acceptable to MSME users due to its intuitive and functional interface.